2020
DOI: 10.1080/07352166.2020.1814154
|View full text |Cite
|
Sign up to set email alerts
|

Perceived reasons for paying more for housing in metro Atlanta: Results from the 2018 Metro Atlanta Speaks survey

Abstract: Various factors may influence housing prices paid by residents, and these factors can be grouped into the demand-or supply-side factors. However, the empirical literature has not adequately investigated whether or not residents perceive that they pay more for housing, and if so, whether paying more is associated with the demand-side factors such as housing attributes or neighborhood/locational amenities, or supply-side factors such as a lack of affordable housing alternatives. Using the 2018 Metro Atlanta Spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…However, previous studies have not confirmed an effect of homeownership on the likelihood of commuting (van Ham and Hooimeijer 2009;Pfaff 2012). One reason for this could be that homeowners are often more involved in locally oriented networks than renters (Blum and Kingston 1984;Ghimire and Skinner 2022). If these networks are used to search for a job, the probability of finding a job in another region is reduced (Abraham and Nisic 2007).…”
Section: Homeownershipmentioning
confidence: 98%
“…However, previous studies have not confirmed an effect of homeownership on the likelihood of commuting (van Ham and Hooimeijer 2009;Pfaff 2012). One reason for this could be that homeowners are often more involved in locally oriented networks than renters (Blum and Kingston 1984;Ghimire and Skinner 2022). If these networks are used to search for a job, the probability of finding a job in another region is reduced (Abraham and Nisic 2007).…”
Section: Homeownershipmentioning
confidence: 98%
“…The definition of community involvement is interpreted broadly because there are formal and informal (Ghimire & Skinner, 2019). Community members play an important role in social life, which is the driving force of various communities (Ghimire & Skinner, 2019).…”
Section: The Effect Of Community Involvement On Purchase Intentionmentioning
confidence: 99%
“…Allowing newcomers the time to integrate and putting them in a position to contribute effectively helps in this regard. For example, new residents may be more likely to volunteer at neighborhood events once they are settled and have become part of the community (Ghimire & Skinner, 2019), and immigrants may be more likely to contribute to charitable organizations once they have secured a job and are integrated in the host country (Bekkers & Wiepking, 2007;Hainmueller et al, 2016). Only by incorporating newcomers, can cooperation for public good provision be sustainable in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that newcomers' contributions are initially lower than those of incumbents but do increase over time resonates with field studies on newcomer contributions. Studies suggest that residents are more likely to volunteer at community events if they are longer part of the community (Ghimire & Skinner, 2019), that workers' output in organizations is higher with higher tenure (Shaw & Lazear, 2008), and that immigrants contribute more to charitable organizations with more time spent in the country (Bekkers & Wiepking, 2007). Typically, these studies only observe individuals at one point in time, so changes over time within individuals as they switch roles are not accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation